2007
DOI: 10.1088/0957-4484/18/25/255705
|View full text |Cite
|
Sign up to set email alerts
|

The interface effect of the effective electrical conductivity of carbon nanotube composites

Abstract: A model of the effective electrical conductivity for carbon nanotube (CNT) composites is presented by incorporating the interface effect with an average field theory. The dependence of the effective electrical conductivity on CNT length, diameter, concentration, and interface properties has been taken care of simultaneously in our treatment so that the model can describe well the interface effect of CNT composites. Predictions from the model are in good agreement with the experimental values of the effective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…A direct-path network of aligned CNTs was observed with $0.5% CNT volume fraction (clearly above the percolation threshold in pure epoxy). Such an improvement is expected, as plastics realize significantly enhanced conductivity at low loadings of unoriented CNTs [30][31][32]. Further, the decrease in through-thickness resistivity is two orders of magnitude greater than the in-plane value.…”
Section: Laminate In-plane and Through-thickness Electrical Resistivimentioning
confidence: 94%
“…A direct-path network of aligned CNTs was observed with $0.5% CNT volume fraction (clearly above the percolation threshold in pure epoxy). Such an improvement is expected, as plastics realize significantly enhanced conductivity at low loadings of unoriented CNTs [30][31][32]. Further, the decrease in through-thickness resistivity is two orders of magnitude greater than the in-plane value.…”
Section: Laminate In-plane and Through-thickness Electrical Resistivimentioning
confidence: 94%
“…Several physics-based computational approaches have been developed for calculating the homogenized electrical conductivity of CNT-polymer composites [15][16][17][18][19][20][21]. In CNT-polymer composites, the CNT-CNT and CNT-polymer interactions are governed by weak non-bonding interactions.…”
Section: Effective Electrical Conductivity Of Carbon Nanotube-epoxy Cmentioning
confidence: 99%
“…P, Q, T and H are constants and are determined using appropriate boundary conditions [17]. The average electrical field intensity in CNTs, E cx , and the interphase, E intx , are given, respectively, by…”
Section: Effective Electrical Conductivity Of Carbon Nanotube-epoxy Cmentioning
confidence: 99%
“…Recently, Yan et al modeled the conductivity of CNT/ polymer nanocomposites. [83] They found that if the intrinsic conductivity of CNTs, dispersed in a polymer matrix increases from 3 Â 10 4 S m À1 to 5.4 Â 10 6 S m À1 , the conductivity of the corresponding nanocomposites can increase by more than one order of magnitude. While it may have been instructive to measure the conductivities of individual IPCNTs and VGCNTs, challenges with isolating and contacting individual CNTs would make these measurements not fully instructive regarding electrical behavior of the composite network.…”
Section: Measurements Performed On Individual Crossed Cnts At Low Biamentioning
confidence: 99%